LIVER BIOPSY IN CHRONIC HEPATITIS C: AN ASSESSMENT OF INTER AND INTRA-OBSERVERS VARIABILITY: Liver Biopsy in Chronic Hepatitis C - Jamal, Shahid; Zubair, Alia; Mubarik, Azhar; Malik, Tariq Masood; Arif, Adeel (Pakistan Armed Forces Medical Journal, 2008)
Objective: To evaluate the inter and intraobserver variability in the histological grading and staging according to modified Knodell scoring system. Design: A cross-sectional comparative study. Place and Duration of study: Histopathology department Army Medical College, Rawalpindi, Pakistan from June 2006 to December 2006, at the Materials and Methods: Slides and original reports of already reported chronic hepatitis C cases were retrieved from the case files. A total of 52 liver biopsies of patients were reevaluated by two pathologists. The inter and intraobserver reproducibility for grade of necroinflammation and stage of fibrosis were calculated by using kappa statistics. Results: For grades of necroinflammation a substantial level of interobserver (kappa=0.802) and intra-observer (kappa= 0.749) reproducibility was found. Disagreement in the interobserver results was detected in 11.5 % cases, with difference of only one grade in all the cases. Disagreement in the intraobserver diagnosis was noted in 15.4% cases, again with the difference of only one grade of necroinflammation. Similarly for the stage of fibrosis, a substantial level of interobserver (kappa= 0.66) and intra-observer (kappa=0.77) reproducibility was present. Main disagreement for interobserver results was of stage 2 and 3 fibrosis. For intraobserver stage of fibrosis, disagreement was found in 9 cases (17.3%). There was disagreement in 6 of the 9 cases with fibrosis stage 3, where original histological stage was reported 4. There were 3 (5.8 %) cases where presence of steatosis was missed (all in non-tabulated form of reports). Conclusion: Substantial level of inter and intra-observer agreement can be achieved, both for the necroinflammatory grade and stage of fibrosis, if the scoring system of chronic hepatitis is strictly followed.